EXPLORING THE IMPACT OF CLOUD TECHNOLOGY ON INDIAN ACCOUNTING: CHALLENGES AND FUTURE OPPORTUNITIES - Dr. Jagruti Ambashankar Purohit (International Educational Journal of Science and Engineering, 2025)
This study explores the transformative impact of cloud technology on Indian accounting practices, highlighting both the challenges faced and the opportunities available in the evolving digital landscape. As the global financial ecosystem rapidly adopts cloud-based systems for enhanced efficiency, scalability, and real-time data access, Indian accountants and businesses are increasingly recognizing the value of this technological shift. The paper provides an in-depth overview of cloud technology, its relevance in global finance, and its gradual emergence within the Indian accounting ecosystem. It discusses the key barriers to adoption such as data security concerns, regulatory uncertainties, infrastructural limitations, and lack of digital literacy, especially among small and medium enterprises (SMEs). At the same time, it emphasizes the vast benefits including automation, cost savings, improved collaboration, and regulatory compliance. The study concludes with strategic recommendations for stakeholders to enable seamless integration of cloud technologies in Indian accounting practices. Overall, the research underscores that while challenges persist, cloud computing offers a robust framework for the future of accounting in India.